2021
DOI: 10.1371/journal.pone.0246352
|View full text |Cite
|
Sign up to set email alerts
|

Mistreatment of newborns after childbirth in health facilities in Nepal: Results from a prospective cohort observational study

Abstract: Background Patient experience of care reflects the quality of health care in health facilities. While there are multiple studies documenting abuse and disrespect to women during childbirth, there is limited evidence on the mistreatment of newborns immediately after childbirth. This paper addresses the evidence gap by assessing the prevalence and risk factors associated with mistreatment of newborns after childbirth in Nepal, based on a large-scale observational study. Methods and findings This is a prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Similarly, the coverage of skin-to-skin contact remained relatively low, despite government prioritisation of this intervention [ 21 ]. The finding is consistent with an observational study of four referral level public hospitals in Nepal which found that skin-to-skin contact was practiced in only 3.50% of babies who breathed spontaneously after birth [ 22 ]. The lack of trained and motivated healthcare staff, along with logistical challenges affects its availability [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, the coverage of skin-to-skin contact remained relatively low, despite government prioritisation of this intervention [ 21 ]. The finding is consistent with an observational study of four referral level public hospitals in Nepal which found that skin-to-skin contact was practiced in only 3.50% of babies who breathed spontaneously after birth [ 22 ]. The lack of trained and motivated healthcare staff, along with logistical challenges affects its availability [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…Healthcare providers’ awareness of implicit bias is not well documented in the context of Nepal and our literature review revealed very few previous studies in Nepal gave this topic even a passing mention37 (for an exception see38). However, it is evident that implicit bias is significantly related to patient-provider interactions, treatment decisions and patient health outcomes in all contexts,33 and certainly will be in Nepal.…”
Section: Discussionmentioning
confidence: 87%